ACE's practical guide to functional anatomy - Newton, Sabrena; Healthy Learning Videos; American Council on Exercise (Monterey, CA : Healthy Learning, 2005)
ACE's Practical Guide to Functional Anatomy, created specifically for personal trainers and group fitness instructors, lays the foundation for understanding how anatomy affects movement. Hands-on learning examples allowthe viewers to apply what they learn to their own bodies. Featuring two separate videos (one that addresses upper-body anatomy and another that reviews lower-body and trunk anatomy), the DVD also covers the basic vocabulary of anatomy, describing gross anatomical structures that are essential knowledge for all fitness professionals. Each muscle description is followed by effective exercises, enabling viewers to apply their knowledge of anatomy in a practical way
ACE's practical guide to functional upper-body anatomy -- ACE's practical guide to functional lower-body anatomy
Title from container
Instructor, Sabrena Newton
DVD format
Keywords: Physical education and training; Exercise -- Physiological aspects; Kinesiology, Applied